Reliability driven constrained job scheduling on volunteer grid resources - Rubab, S. (American Scientific Publishers, 2016)
The job scheduling in grids is a NP-hard problem. Many attempts has been made to solve the job scheduling using different methods. Constraint based job scheduling is evolving in volunteer grid computing environments. The constraint based scheduling provides information about the job requirements like time, cost etc. The paper proposes a job scheduling heuristic to maximize the schedule reliability. The heuristic first choose the capable resources and will assign one of the resources from set which can satisfy the job constraint based on the reliability of schedule. The reliability of schedule has been derived from the closeness of deadline. The simulation results show the significance of closeness of deadline for finding the reliable schedule using the proposed reliability driven job scheduling heuristic. Â© 2016 American Scientific Publishers. All rights reserved.